2020
DOI: 10.2147/rru.s238746
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Management of Bladder Pain Syndrome/Interstitial Cystitis: A Review on Current Recommendations and Emerging Treatment Options</p>

Abstract: Bladder pain syndrome (BPS) is a chronic condition characterized by pelvic pain or pressure which is perceived to be originating from the bladder, accompanied by one or more urinary symptoms, including frequency, urgency and nocturia. The precise etiology of BPS is not fully understood. Chronic bacterial infection, defective glycosaminoglycan (GAG) layer of the bladder urothelium, inappropriate activation of mast cells in the suburothelial layer of the bladder, autoimmune-mediated mechanisms and autonomic nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 79 publications
0
30
0
3
Order By: Relevance
“…Although the exact cause of IC is inadequately perceived, however different hypothesis suggest various causative factors that may include disturbance in the urothelium lining permeability of the bladder due to deficiency of glycosaminoglycan (GAG), immune system actuation, pole cell penetration, neurogenic mechanisms or any infection. 12 Approximately 5-10% of patients will have ulcerations in the bladder, known as Hunner's injuries (HL) 13 related to more extreme indications and diminished bladder limit. Although it is beyond the realm of possibilities to recognize patients with HL on the basis of manifestations alone, utility of cystoscopy shift between rules, sometimes mandatory and sometimes optional.…”
Section: Diagnosis and Current Treatment Modalities For The Managemen...mentioning
confidence: 99%
“…Although the exact cause of IC is inadequately perceived, however different hypothesis suggest various causative factors that may include disturbance in the urothelium lining permeability of the bladder due to deficiency of glycosaminoglycan (GAG), immune system actuation, pole cell penetration, neurogenic mechanisms or any infection. 12 Approximately 5-10% of patients will have ulcerations in the bladder, known as Hunner's injuries (HL) 13 related to more extreme indications and diminished bladder limit. Although it is beyond the realm of possibilities to recognize patients with HL on the basis of manifestations alone, utility of cystoscopy shift between rules, sometimes mandatory and sometimes optional.…”
Section: Diagnosis and Current Treatment Modalities For The Managemen...mentioning
confidence: 99%
“…It is preferable for patients with refractory BPS who are not sensitive to other oral or intravesical agents. 48 Intravesical dimethylsulfoxide (DMSO) demonstrated high efficacy in symptom improvements and urodynamic and voiding diary changes with minor side effects. 49 In addition, DMSO remains the only approved drug by the Food and Drug Administration (FDA) to treat IC/BPS, and it is hypothesized to inhibit inflammatory mast cells and promote the relaxation of bladder muscles.…”
Section: Standard Treatments For Ic/bpsmentioning
confidence: 99%
“…The precise etiology of IC is still ambiguous, and multiple theories have been suggested, including endothelial permeability, subclinical infection, autoimmunity, neurologic abnormality and genetic susceptibility [ 5 , 6 ]. Owing to the complex pathogenesis, current therapies for IC are not satisfactory and only provide partial relief [ 2 , 7 ], highlighting the urgent need to develop new effective treatment options for IC. Our previous studies have demonstrated that neuroinflammation in the spinal dorsal horn (SDH) contributes to bladder hypersensitivity and plays a pivotal role in the pathogenesis of IC [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%